2020
DOI: 10.4038/jnsfsr.v48i2.9565
|View full text |Cite
|
Sign up to set email alerts
|

Total and free amino acid contents of popular rice varieties (Oryza sativa L.) consumed in the capital city of Sri Lanka

Abstract: This study investigated the amino acid composition of eight local and three imported rice varieties frequently consumed by consumers in the capital of Sri Lanka. Investigation included twenty free amino acids (FAAs) analysed using liquid chromatography-tandem mass spectrometry (LC-MS/MS) and sixteen protein bound amino acids analysed using high performance liquid chromatography with diode array detection (HPLC-DAD). The mean total amino acid (TAA) in rice ranged between 64.5 ± 1.9 g/kg and 96.0 ± 5.1 g/kg on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…This method was validated (Liyanaarachchi et al, 2020a), and the performance characteristics of the method as indicated in Table 1 were found in compliance with the requirements specified in the international method guidelines for method validation.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…This method was validated (Liyanaarachchi et al, 2020a), and the performance characteristics of the method as indicated in Table 1 were found in compliance with the requirements specified in the international method guidelines for method validation.…”
Section: Methodsmentioning
confidence: 94%
“…The column was operated at 40°C. The detection of FAAs was performed using an Eksigent Expert Ultra LC 100 XL (Eksigent, Netherlands) UPLC system, coupled to an ABSciex (QTrap) 4500 series triple quadrupole linear ion trap mass spectrometer (Sciex, USA) in electro spray ionization (ESI) with multiple reaction monitoring (MRM) transitions (Supplementary Table S1) for the detection of FAAs including GABA as specified by Liyanaarachchi et al (2020a). The ion spray voltage was set at 5500 V, while the source temperature was maintained at 500°C.…”
Section: Analysis Of Faas Including Gabamentioning
confidence: 99%
“…FAAs were analyzed using an automatic amino acid analyzer (S‐4330D, Sykam, Munich, Germany) according to the method of Liyanaarachchi et al 17 …”
Section: Methodsmentioning
confidence: 99%
“…FAAs were analyzed using an automatic amino acid analyzer (S-4330D, Sykam, Munich, Germany) according to the method of Liyanaarachchi et al 17 Volatile flavor substances analysis Gas chromatography-mass spectrometry (GC-MS) was applied to determine the content of volatile flavor substances and 2-octanol was used as the internal standard according to our previous publication. 18 Each rice wine sample was diluted with deionized water to a final concentration of 6% (v/v) ethanol.…”
Section: Faa Analysismentioning
confidence: 99%
“…Apart from dietary carbohydrates, rice also contains proteins, lipids, minerals, and vitamins (Fageria 2015 ). The annual per capita consumption of rice in Sri Lanka is 105 kg indicating the major contribution of rice to the Sri Lankan diet (Jayatissa et al 2014 ; Liyanaarachchi et al 2020 ). Moreover, the daily rice consumption is 300.6 g/capita/day in Sri Lanka, ranking at the 9th highest in the world.…”
Section: Introductionmentioning
confidence: 99%